Improving School Health Literacy for Teachers-Students-Parents as Steps to Control Covid-19 Transmission Regarding School Re-Opening Attempts - Fernanda, Enrico Faiz; Nisa, Shafira Aulia; Santoso, Richard Kevin; Wening, Gilang Rasuna Sabdho; Setijanto, R. Darmawan; Setyowati, Dini; Wulandari, Primatia Yogi; Siswantara, Pulung (Indonesian Journal of Dental Medicine, 2021)
Background: The Covid-19 pandemic has changed all activities into nearly completed by online action. in online teaching and learning activities, students interact a little and less socializing with peers who are feared to affect the level of students' confidence and ability to socialize during teaching and learning activities in class re-opening. Purpose: To prepare mental and psychological conditions of students in offline teaching and learning activities, also pays attention to measure the readiness of teachers in school re-opening attempt. Methods: Prepare mental condition and psychic students in offline teaching and learning activities, by increasing the readiness of teachers in the implementation of offline teaching and learning activities, as well as assessing the effectiveness of students' psychological and mental character development activities in facing offline teaching and learning activities. Results: The results of the pre-test about the readiness to release the child during the teaching and learning process carried out offline in the midst of the Covid-19 Pandemic dominated by the answer "Very” not ready” with a percentage of 43.80%; "ready” answers as many as 30.43%. In addition, respondents the percentage of those who choose the "Ready” option in the post-test is higher, namely 26.09% compared to the pre-test which was only 7.44%. Conclusion: Efforts are applied to prepare students' physical and psychological conditions in offline teaching and learning activities in anticipation of the impact of post-based education digital service carried out by the community service team are successfully triggered the readiness of teachers and facilities at the school is considered to be ready, based on after consideration carry out three work programs that are reviewed from very good facilities adequate, strictly enforced health protocols, as well as teaching staff who are able to carry out health promotion campaigns withfluent.